Pleistocene Reptiles of The Soa Basin (Flores, Indonesia): Adaptation and Implication for Environment - Erick Setiyabudi (Jurnal Geologi dan Sumberdaya Mineral, 2016)
The presence of fossil reptiles from the mainland of Asia, such as: giant tortoise (Megalochelys sp.), fresh water turtle (Geoemydidae), crocodile (Crocodylus sp.) and the komodo dragon (Varanus komodoensis) in the Soa Basin of Flores, supports the hypothesis that Wallace's line is not a demarcation line between the reptilian fauna from Asia (Indo-Malayan region) and that from Australia (Austro-Malayan region) in the reptiles came to Flores about 1 million years ago, or perhaps earlier (during the Pleistocene), by sweep stake dispersal through swimming or floating. After arrived, they lived in isolated conditions and adapted to a savannah environment. Nevertheless no morphological changes with their Asian mainland ancestors could be found.